PENGEMBANGAN BUKU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN BERWAWASAN NUSANTARA UNTUK SD KELAS III GUNA MEMPERKUAT PROFIL PELAJAR PANCASILA - Dian Nastiti; Lupita Ariantika Sari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The lack of innovative learning media in Civic Education at Madrasah Ibtidaiyah can be a hindrance to the achievement of learning goals and the development of the Pancasila student profile. The conducted research was centered on the development of a companion civic education book for third-grade elementary school students based on the archipelago insight (PAKTARA) with the theme of rights and obligations. The implementation of this research utilized the R&D research method according to Borg & Gall's version. The process was simplified into three stages: preliminary study, product development, and product testing. The validation results of the instructional media by media experts, subject matter experts, and language experts yielded a score of 90%, indicating its validity for use as a student companion book falling under the category of highly suitable or excellent due to the validation percentage falling within the range of 81—100%. The PAKTARA book media also fulfilled the students' learning needs, as indicated by an 85% questionnaire response rate, and exhibited a positive impact on enhancing the students' comprehension of the archipelago-based rights and obligations content, contributing to the advancement of the pancasila learners' profile.